Konsentrasi lemak dan kolesterol daging broiler pada berbagai tingkat pemberian tepung daun indigofera (Indigofera zollingeriana) dalam Ransum - Zakaria Syifa Nugraha; Rachmat Somanjaya; Lili Adam Yuliandri (Fakultas Pertanian Universitas Majalengka, 2025)
This study aims to analyze the lipid and cholesterol content of broiler chicken meat from fish meal and soybean meal substitution with Indigofera leaf meal (Indigofera zollingeriana) (TDI) in the Ration and to obtain the balance of Indigofera leaf meal substitution to produce the best lipid and cholesterol content of broiler chicken meat. The study was conducted experimentally for 35 days using a Completely Randomized Design (CRD). The treatments given were in the form of substitution (TDI) at five levels, namely: 0% P0 (as control), P1 = Ration + 25% TDI; P2 = Ration + 30% TDI; P3 = Ration + 35% TDI; P4 = Ration + 40% TDI. Each treatment was repeated 4 times, and each replication unit kept five chickens, so the total required was 100 chickens. The variables observed were the lipid and cholesterol content of meat. The data obtained were analyzed by ANOVA and continued with Duncan's multiple range test. The results showed that the lipid content of broiler meat was not significantly affected (p>0.05) by TDI substitution. The same thing happened to the cholesterol content of broiler meat, which was not significantly affected (p>0.05) by TDI substitution. The highest lipid content was found in the P0 treatment, which was 6.75%, and the lowest was found in the P4 treatment, which was 4.70%. However, the lipid content of meat in all treatments was classified as usual. Meanwhile, the lowest cholesterol content, 77.31 mg/100g, was found in P2, and the highest, 84.05 mg/100g, was found in the P3 treatment. It can be concluded that the addition of TDI can reduce lipid and cholesterol content at certain levels, although the difference is not significant.